2021
DOI: 10.3390/ani11061831
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence That Bird Feeders Are a Source of Salmonellosis during Winter in Poland

Abstract: Bird feeders are known to be a transfer site for many important bird pathogens, such as zoonotic Salmonella spp., known to be widespread among wild birds in Poland. The aim of the study was to investigate (1) whether feeders can be a source of Salmonella spp., (2) whether the risk is the same for feeders located in cities and rural areas and (3) whether there is a different level of contamination with Salmonella spp. between old and new feeders. Data were collected in the period 12 January–28 February 2018 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…For example, feeding wild birds is often actively encouraged, particularly during winter, providing the feedstuff is appropriate [ 22 ]. Although concerns have been raised that such supplemental feeding results in dependency and increases the spread of infectious diseases, the evidence that this is the case is often not clear cut [ 23 , 24 , 25 , 26 ], and typically bird feeding has been associated with improved health and survival rates [ 25 , 27 ]. Feeding other species of wild or free-ranging animals is generally not as common as feeding garden birds, although there are indicators that this is changing, e.g., with the increased availability of food for hedgehogs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, feeding wild birds is often actively encouraged, particularly during winter, providing the feedstuff is appropriate [ 22 ]. Although concerns have been raised that such supplemental feeding results in dependency and increases the spread of infectious diseases, the evidence that this is the case is often not clear cut [ 23 , 24 , 25 , 26 ], and typically bird feeding has been associated with improved health and survival rates [ 25 , 27 ]. Feeding other species of wild or free-ranging animals is generally not as common as feeding garden birds, although there are indicators that this is changing, e.g., with the increased availability of food for hedgehogs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…on sugar water feeders themselves. Although some studies have not detected this pathogen on urban bread and seed feeders, 81,82 a New Zealand study (Auckland) showed that up to 7% of sampled feeders were positive for Salmonella spp. 16 One of the most common bread and seed feeder visitors in that study was the house sparrow, which also was shown to carry Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Din acest considerent, scopul investigațiilor propuse a fost de a stabili incidența circulației serotipelor patogene de Salmonella spp. în materiile fecale și materialul patologic prelevat de la întreprinderile avicole, destinate producerii cărnii de pasăre și a ouălor de consum curent [2,10,12].…”
Section: Introducereunclassified